الثقافة التنظيمية وأثرها في الابتكار التنظيمي: دراسة عن موظفي الجامعة مصراتة (Journal of Academic Research, 2026)
This research aims to explore the impact of organizational culture on organizational innovation at Misrata University, with a particular focus on identifying the cultural dimensions most influential in fostering innovative practices. To achieve this objective, the study adopted a descriptive-analytical approach. Data were collected through a questionnaire distributed to a random sample of 130 employees at the university, allowing for an analysis of the existing cultural environment and its support for the innovation process within the academic institution.The results revealed a strong and statistically significant positive correlation between the dimensions of organizational culture and innovation. These dimensions accounted for 42.8% of the variance in the level of organizational innovation. While "collaboration culture" emerged as the most prevalent element within the university environment, the study indicated a deficiency in "incentive culture." This necessitates the development of reward and incentive systems to support creative initiatives and activate the roles of autonomy and calculated risk-taking within the workplace.